Lope’s El Hamete de Toledo: the infidel’s body as conquered land - García Soormally, Mina (Body and religion, 2019)
Set in the aftermath of the 1609 expulsion of the Moriscos decreed by King Philip III of Spain (r. 1598-1621), the play El Hamete de Toledo, by Lope de Vega, has found a new relevance on stage and in political debates linked to the current immigration crisis. This article aims to rethink the current victimization of Muslims, as presented in the production of AlmaViva Teatro, a Spanish theater company which used the Early Modern Spanish tragedy to connect to a contemporary audience, thirsty for social justice. To this end, I will focus on the treatment of Hamete, a Moor imprisoned in Spain, and whose body becomes the symbol of the Other, to be conquered. As such, in the course of the play, his body is vilified, dehumanized, chained, and tortured. The culmination of this process coincides with the final act of surrender, the moment of his conversion, but also of the physical dismemberment of his body, a brutal ritualistic sacrifice carried out in the name of eternal salvation.